2014
DOI: 10.1007/s11596-014-1348-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative protective effect of icariin on the FeSO4/H2O2-damaged human sperm based on confocal raman micro-spectroscopy

Abstract: Oxidative stress is implicated in male infertility and significantly higher reactive oxygen species are detected in 25% of infertile males. Although different agents of various alternative medicines, including traditional Chinese medicine, have been tried with varying success, evidence remains limited on whether and how much herbs or supplements might help increase the anti-oxidant ability of the sperm. This study examined the anti-oxidative effects of icariin, a flavonoid isolated from Herba Epimedii, on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Excessive deposition of inflammatory cytokines in the microenvironment of intervertebral disc contributes to degeneration of the intervertebral disc [ 28 ]. As a traditional Chinese medicine, icariin has a strong antioxidative [ 29 32 ] and anti-inflammatory effect [ 33 36 ] in many vital tissues; however, there were no studies reporting its effect in the intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive deposition of inflammatory cytokines in the microenvironment of intervertebral disc contributes to degeneration of the intervertebral disc [ 28 ]. As a traditional Chinese medicine, icariin has a strong antioxidative [ 29 32 ] and anti-inflammatory effect [ 33 36 ] in many vital tissues; however, there were no studies reporting its effect in the intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants and their active ingredients have received greater attention as potential anti-peroxidative agents. Icariin (ICA), (C 33 H 40 O 15 ; molecular weight: 676.67), the main active flavonoid glucoside from Epimedium herba is associated with a wide range of pharmacological and biological activities, including anti-inflammatory, antidepressant, anti-tumor activity, antioxidant effect, estrogenic activity, cardiovascular protection, enhancement of bone healing and neuroprotection, immunoregulation, and improved sexual function [9][10][11][12]. Experiment on animals has revealed that ICA improves erectile function when administered to aged male rats [13].…”
Section: Introductionmentioning
confidence: 99%
“…Icariin (ICA) is a natural flavonoid glycoside isolated from plants in the Epimedium genus (Yin-Yang-Huo) of the Berberidaceae family and a well-known traditional Chinese medicine for treating male sexual dysfunctions, such as erectile dysfunction and premature ejaculation (9,10). ICA, the major and active compound of Epimedium, has been associated with many biological and pharmacological effects, such as anti-osteoporotic (11), antioxidative (12), anti-inflammatory (13), anti-cancer (14), anti-depressant (15) and neuro-protective effects (16). Previous studies have reported that ICA ameliorates various diseases, including atherosclerosis, asthma and erectile dysfunction (17)(18)(19); however, the therapeutic effects of ICA in acute pancreatitis require further investigation.…”
Section: Introductionmentioning
confidence: 99%